Perioperative ventilatory strategies in cardiac surgery. Issue 3 (September 2015) - Lellouche, François; Delorme, Mathieu; Bussières, Jean; Ouattara, Alexandre
Abstract : Recent data promote the utilization of prophylactic protective ventilation even in patients without acute respiratory distress syndrome (ARDS), and especially after cardiac surgery. The implementation of specific perioperative ventilatory strategies in patients undergoing cardiac surgery can improve both respiratory and extra-pulmonary outcomes. Protective ventilation is not limited to tidal volume reduction. The major components of ventilatory management include assist-controlled mechanical ventilation with low tidal volumes (6–8 mL kg −1 of predicted body weight) associated with higher positive end-expiratory pressure (PEEP), limitation of fraction of inspired oxygen (FiO2 ), ventilation maintenance during cardiopulmonary bypass, and finally recruitment maneuvers. In order for such strategies to be fully effective, they should be integrated into a multimodal approach beginning from the induction and continuing over the postoperative period.